A revision of Biting Midges of the Subgenera Forcipomyia (Metaforcipomyia) and F. (Saliohelea) from Costa Rica (Diptera: Ceratopogonidae) - Spinelli, Gustavo R.; Marino, Pablo I.; Borkent, Art (Zootaxa, 2012)
The Costa Rican species of the subgenus Forcipomyia (Metaforcipomyia) Saunders are revised, primarily based on males. Fourteen new species are described and illustrated, F. (M.) pluvialis Malloch is redescribed, and a key to males and females is provided. One new species of the subgenus Forcipomyia (Saliohelea) Wirth & Ratanaworabhan is described and illustrated and F. (S.) leei Wirth & Ratanaworabhan is redescribed. Forcipomyia (Euprojoannisia) pechumani Bystrak & Wirth is transferred to the subgenus F. (Saliohelea). All adult F. (Metaforcipomyia) lack a hind tibial comb and males have antennal flagellomeres 5–8 fused and these are proposed synapomorphies of the subgenus. A truncate labrum is present in F. pluvialis, F. rivalis n. sp. and F. truncata n. sp. and is a derived feature indicating these species form a monophyletic group. We were unable to suggest a synapomorphy indicating the monophyly of F. (Saliohelea). Nearly all Costa Rican members of the subgenera F. (Metaforcipomyia) and F. (Saliohelea) are restricted to wet habitats and are excluded from the dry northwestern portion of this country. Eleven of the 15 new species described herein are present in the lowlands of Costa Rica, suggesting they are actually more broadly distributed to the north and/or south.